2020
DOI: 10.3390/app10134521
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Sonication and Acid Whey on Antioxidant and Angiotensin-Converting Enzyme Inhibitory Activities of Peptides Obtained from Dry-Cured Pork Loin

Abstract: This study aimed to determine the effects of sonication and acid whey maceration on the oxidative stability, antioxidant activity and angiotensin-converting enzyme (ACE) inhibitory activity of peptides obtained from dry-cured pork loins. The changes in the selected parameters were documented over 7, 21 and 42 days of storage. The lowest antioxidant and angiotensin-converting enzyme inhibitory activities of peptides were noted in batches with curing salt (C) and acid whey (SW) compared to batches with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…It has been shown that changes in the basic meat components during production changed the chemical composition of the products as compared to the properties of the raw material. The values of the physicochemical properties of raw material used for fermented loin production were typical for goodquality fresh pork and similar to those obtained by Kęska and Stadnik [31]. Water loss during drying, by almost 10% compared to the moisture content in raw material, resulted in a higher concentration of nutrients, especially proteins.…”
Section: Discussionsupporting
confidence: 82%
“…It has been shown that changes in the basic meat components during production changed the chemical composition of the products as compared to the properties of the raw material. The values of the physicochemical properties of raw material used for fermented loin production were typical for goodquality fresh pork and similar to those obtained by Kęska and Stadnik [31]. Water loss during drying, by almost 10% compared to the moisture content in raw material, resulted in a higher concentration of nutrients, especially proteins.…”
Section: Discussionsupporting
confidence: 82%
“…According to Uluko et al [ 42 ], the shear forces generated by acoustic cavitation during ultrasonic treatment can hydrolyze proteins, leading to the release of bioactive peptides. Nevertheless, as shown earlier [ 43 ], treatment with ultrasound as a preliminary stage in the preparation of raw pork meat tissue (as a process preceding maceration of loins in acid whey) did not promote the release of antioxidant or ACE-I inhibitory peptides. This relationship suggests the use of simultaneous maceration in sour milk and the action of ultrasound lead to the formation of biologically active peptides in meat tissue.…”
Section: Discussionmentioning
confidence: 56%
“…Fermented meat products are appreciated by consumers not only for their unique taste and aroma, but also for their health benefits. Several studies have revealed that these products are the source of biologically active peptides [2][3][4]. The presence of these compounds is associated with the fermentation process, which results in proteolytic changes in proteins leading to the formation of peptides and amino acids.…”
Section: Introductionmentioning
confidence: 99%